Building legitimacy : political discourses and forms of legitimacy in medieval societies - Alfonso Antón, Isabel; Kennedy, Hugh (Hugh N.); Escalona, Julio (Medieval Mediterranean, 2004)
This volume presents a selection of papers exploring the ways by which medieval powers sought to legitimize themselves, the political discourses through which this was effected and a wide range of related problems.